Keabsahan Kepemilikan Tanah yang Diperoleh Berdasarkan Perjanjian Nominee Antar Sesama Warga Negara Indonesia - Achmad Hariyadi; Rusdianto Sesung (Jurnal Selat, 2021)
Nominee agreements related to land ownership in Indonesia occur a lot in terms of land ownership by foreign nationals. Until now, there is not a single statutory regulation that prohibits the existence of a nominee agreement if the legal subject is a fellow Indonesian citizen, thus giving birth to a norm vacuum (rechtsvacuum). This study analyzes the validity of nominee agreements with land objects made between Indonesian citizens. This research is normative legal research using a statute approach and conceptual approaches. The results of the study indicate that the nominee agreement made by fellow Indonesian citizens with an object in the form of land legally applicable in Indonesia is valid and binding for the parties bound by the agreement if it is carried out in accordance with the legal terms of the agreement stipulated in the Civil Code. As mentioned above, the provisions of Article 26 paragraph (2) of the Basic Agrarian Law, if interpreted as a contrario, can be concluded that it is not prohibited if the nominee agreement is made between Indonesian citizens.